Tata Kelola Kolaboratif dalam Pelaksanaan Program Padat Karya di Kecamatan Semampir Kota Surabaya - Lutfiatul Laili Arrohmati; Oktarizka Reviandani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Labor-intensive programs are one of the strategies employed by the Surabaya city government to alleviate poverty in Surabaya. Labor-intensive programs are initiatives that aim to empower poor communities by utilizing natural resources, labor, and local technology. The main objective of these labor-intensive programs is to increase income and provide employment opportunities for poor communities. This study aims to analyze and describe in depth the collaborative governance in the implementation of the labor-intensive program in Semampir District, Surabaya City, using Ansell and Gash's (2008) theory, which includes four variables: (1) initial conditions; (2) institutional design; (3) facilitative leadership; and (4) collaborative process. This study employs a qualitative descriptive research method with informant selection using purposive sampling. The results indicate that: (1) The initial conditions of the program exhibit an imbalance of power, resources, and knowledge, making it difficult for the community to access information. (2) Institutional design, which includes active stakeholder participation, limited forums, and basic rules, has been implemented effectively. (3) Facilitative leadership, carried out by the Mayor of Surabaya and the Regional Development Planning Agency (Bappedalitbang), involves planning and organizing community-based work programs. (4) The collaborative process conducted by each stakeholder is sufficiently effective. Although collaborative governance in the implementation of labor-intensive programs in Semampir subdistrict faces a number of challenges, collaboration between various actors can accelerate the achievement of program objectives.